Archimedia - Meyer, Marina Therese (My University, 2008)
This thesis will attempt to expose and understand the relationship between media and architecture (‘Archimedia’). This relationship has been around for centuries. The only constant in this relationship is change and this is what people have come to rely on. ‘Archimedia’ embraces this instability and sees it as an opportunity for a rejuvenation of the architectural language.
Keywords: media; architecture